Using Syntactical Devices in A Speech - Mardonova Mohidil Musurmonovna (Zien Journals, 2021)
This article describes in detail the use of syntactic tools in speech, the functional styles of literary speech, and the important functions of speech appearances.
Keywords: Functional style; scientific style; journalistic style; conversational style; artistic style